Site tenacity of the Long-tailed Skua Stercorarius longicaudus—a study of the population at Stekenjokk - Larsson, Rolf (Ornis Svecica, 2007)
The breeding site tenacity of a population of Long-tailed Skuas Stercorarius longicaudus at Stekenjokk in the northern part of Jämtland was studied in an area of 27 km2 between 2001 and 2006. At least one bird in a pair was ringed for identification. The Long-tailed Skua had pronounced breeding site tenacity. The established pairs returned to and stayed in their territories even in bad rodent years when they did not breed. One bird was recorded in the same territory all six years. Since both birds of a pair were usually not ringed it was observed only once that the same birds were mated in the same territory in two years. From one year to another they normally moved their nest only a short distance within the territory. The number of rodents in the area had a large influence on the number of Long-tailed Skuas breeding and also tended to affect the number of eggs in the broods. In extremely bad rodent years the Long-tailed Skuas deserted the area prematurely.